The Importance of Context in Screening in Occupational Health Interventions in Organizations: A Mixed Methods Study - Vignoli, Michela; Nielsen, Karina; Guglielmi, Dina; Tabanelli, Maria C.; Violante, Francesco S. (Frontiers in Psychology, 2017)
In occupational health interventions, there is a debate as to whether standardized or tailored measures should be used to identify which aspects of the psychosocial work environment should be targeted in order to improve employees’ well-being. Using the Job Demands-Resources model, the main aim of the present study is to demonstrate how a mixed methods approach to conducting screening enables the identification of potential context-dependent demands and resources in the workplace, which should to be targeted by the intervention. Specifically, we used a mixed methods exploratory sequential research design. First, we conducted four focus groups (N = 37) in a sample of employees working in grocery stores in Italy. The qualitative results allowed to identify one possible context-specific job demand: the use of a work scheduling IT software, whose implementation resulted in a high rotation between different market’s departments. From the qualitative results, this context-specific demand seemed to be related to workers’ well-being. Thus, in a subsequent questionnaire survey (N = 288), we included this demand together with generic measures of social support and psychological well-being. Results confirmed that this context-specific job demand was related to emotional exhaustion. Furthermore, it was found that social support moderated the relationship between this specific job demand and emotional exhaustion showing among employees whose activites depended on the IT software, employees that perceived higher levels of social support from colleagues experienced lower levels of emotional exhaustion with respect to their colleagues who perceived lower levels of social support. The present study confirms that mixed methods approach is useful in occupational health intervention research and offers a way forward on helping organizations prioritize their intervention activities.